2004
DOI: 10.1002/j.2333-8504.2004.tb01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Personality Domains in Relation to Occupational Choice and Performance Among Established Teachers

Abstract: Does personality impact differently on occupational choice and occupational performance? In a study of established teachers, interests, the Five-Factor Model, and attributions were examined in relation to occupational choice and performance. Attributions were assessed using a new instrument designed for teachers. Choice of teaching specialty was found to be most strongly associated with interest in the arts and sciences, openness to experience, and internal attributions in response to a positive classroom even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For math and science teachers in particular, Ingersoll and May (2010) noted i) frequency of student discipline problems, ii) extent of professional development in classroom management, and iii) effectiveness of subject-area professional development as predictors of attrition. Likewise, Emmerich, Rock, and Trapani (2004) found that attribution of classroom events differed between math and science teachers and teachers of other subjects, noting that "compared to other secondary school teachers (especially high school teachers of English), teachers of science experience relatively low sense of control in response to a negative classroom event" (p. 30).…”
Section: Survey Of Teacher Attrition Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For math and science teachers in particular, Ingersoll and May (2010) noted i) frequency of student discipline problems, ii) extent of professional development in classroom management, and iii) effectiveness of subject-area professional development as predictors of attrition. Likewise, Emmerich, Rock, and Trapani (2004) found that attribution of classroom events differed between math and science teachers and teachers of other subjects, noting that "compared to other secondary school teachers (especially high school teachers of English), teachers of science experience relatively low sense of control in response to a negative classroom event" (p. 30).…”
Section: Survey Of Teacher Attrition Researchmentioning
confidence: 99%
“…The claim by Emmerich, Rock, and Trapani (2004) that attribution of classroom events differed between math and science teachers and teachers of other subjects, may be associated with level of conscientiousness. Again, however, studies by Rockoff, Jacob, Kane, and Staiger (2008) contradict this assertion, leaving questions about personality differences between math and science teachers and teachers of other subjects for future research.…”
Section: Should Statementsmentioning
confidence: 99%
“…For example, Emmerich, Rock, & Trapani (2004) developed the Teacher Attribution Inventory-Short Form (TAI-S) to measure characteristic attribution patterns for teachers in a study of determinants of teaching success. The instrument assesses causal attributions for a successful and for an unsuccessful teaching event.…”
Section: Self-reportsmentioning
confidence: 99%